2011
DOI: 10.1166/jnn.2011.4336
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of Tunnel Resistance of Nanogaps by Field-Emission-Induced Electromigration Using Current Source Mode

Abstract: A newly investigated technique for the tuning of the tunnel resistance of nanogaps using electromigration method induced by a field emission current is presented to reduce the power consumption during the process. The method is called "activation" and is demonstrated with a current source. Planar-type initial nanogaps of Ni separated by 20-80 nm were defined on SiO2/Si substrates via electron-beam lithography and the lift-off process. Then, a bias current was applied to the initial nanogaps at room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In our previous work, the tunnel resistance of nanogaps can be controlled by only the magnitude of the field emission current during the activation [9][10][11]. Therefore, it is expected that one can tune the resistance of nanogaps more precisely, in which the gap is sufficiently narrowed even at the final stage of activation, with a feedback control scheme.…”
Section: Tuning Of Resistance Of Nanogaps Using Field-emission-inducementioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, the tunnel resistance of nanogaps can be controlled by only the magnitude of the field emission current during the activation [9][10][11]. Therefore, it is expected that one can tune the resistance of nanogaps more precisely, in which the gap is sufficiently narrowed even at the final stage of activation, with a feedback control scheme.…”
Section: Tuning Of Resistance Of Nanogaps Using Field-emission-inducementioning
confidence: 99%
“…However, the nanogap electrodes fabricated by this method tend to exhibit high tunnel resistance [7,8]. We have already reported that the control of tunnel resistance of nanogap electrodes is performed by field-emission-induced electromigration, which is the so called "activation" [9][10][11]. The advantage of this method is that the tunnel resistance of nanogaps can be extensively tuned by only the magnitude of the field emission current during activation.…”
Section: Introductionmentioning
confidence: 99%
“…We call this "activation" method. The activation method is based on moving the atoms induced by the Fowler-Nordheim (F-N) field emission current passing through the nanogaps between source and drain electrodes [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In the activation procedures, it is expected that the moved atoms accumulate within the gaps and play the dual role of reducing the gap width and forming SETs islands [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The activation method is based on moving the atoms induced by the Fowler-Nordheim (F-N) field emission current passing through the nanogaps between source and drain electrodes [6][7][8][9][10][11][12][13]. In the activation procedures, it is expected that the moved atoms accumulate within the gaps and play the dual role of reducing the gap width and forming the SETs islands [12,13].…”
Section: Introductionmentioning
confidence: 99%